2003
DOI: 10.1080/14734220310022289
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of calcium-binding proteins in the cerebellum

Abstract: Calcium plays a fundamental role in the cell as second messenger and is principally regulated by calcium-binding proteins. Although these proteins share in common their ability to bind calcium, they belong to different subfamilies. They present, in general, specific developmental and distribution patterns. Most Purkinje cells express the fast and slow calcium buffer proteins calbindin-D28k and parvalbumin, whereas basket, stellate and Golgi cells the slow buffer parvalbumin only. They are, almost all, calretin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
182
2
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(202 citation statements)
references
References 129 publications
15
182
2
3
Order By: Relevance
“…Their phenotypes were determined on the basis of several criteria, including (1) morphological features, (2) expression of type-specific markers, (3) morphometric parameters (e.g., cell body size), and (4) position in the host cortical layers or deep nuclei. The different types of GABAergic interneurons were identified according to the expression pattern of a set of distinctive markers and assigned to different categories: deep nuclei interneurons [NeuN/calretinin (Bastianelli, 2003;Weyer and Schilling, 2003)]; granular layer interneurons for Golgi [mGluR2/Pax-2 Grimaldi and Rossi, 2006)] and Lugaro cells [calretinin (Dino et al, 1999;Bastianelli, 2003)]; and molecular layer interneurons for basket and stellate cells [parvalbumin (Celio, 1990)]. Except for rare elements ectopically positioned in the white matter (see below and Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their phenotypes were determined on the basis of several criteria, including (1) morphological features, (2) expression of type-specific markers, (3) morphometric parameters (e.g., cell body size), and (4) position in the host cortical layers or deep nuclei. The different types of GABAergic interneurons were identified according to the expression pattern of a set of distinctive markers and assigned to different categories: deep nuclei interneurons [NeuN/calretinin (Bastianelli, 2003;Weyer and Schilling, 2003)]; granular layer interneurons for Golgi [mGluR2/Pax-2 Grimaldi and Rossi, 2006)] and Lugaro cells [calretinin (Dino et al, 1999;Bastianelli, 2003)]; and molecular layer interneurons for basket and stellate cells [parvalbumin (Celio, 1990)]. Except for rare elements ectopically positioned in the white matter (see below and Fig.…”
Section: Methodsmentioning
confidence: 99%
“…2 A, 3A, B) (Jankovski et al, 1996), whereas the latter stains smaller ovoid-shaped cells (Figs. 2 A, 3 E, F ) (Bastianelli, 2003). Hoshino et al (2005) reported that the SMI32-positive cells do not colabel with anti-GABA antibodies and represent the large glutamatergic projection neurons.…”
Section: Birthdates Of Deep Nuclei Neuronsmentioning
confidence: 99%
“…Calbindin D28k (CaB), a member of calcium-binding protein superfamily, is a PCspecific protein in the cerebellum (Bastianelli, 2003). CaB has six EF-hand motifs, serves as a cytosolic calcium buffer, and plays an important role in motor functions (Schwaller et al, 2002;Simons and Pellionisz, 2006;Whitney et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…These closely related cytosolic proteins bind free Ca 2ϩ -ions and thus contribute to the fast Ca 2ϩ -buffer capacity of cells. Strong expression of calbindin in cerebellar Purkinje cells was demonstrated by immunohistochemistry (Celio, 1990;Fortin et al, 1998;Bastianelli, 2003), whereas granule cells express calretinin (Resibois and Rogers, 1992;Marini et al, 1997;Bearzatto et al, 2005). In contrast, only a faint expression of calbindin was shown in the IC (Celio, 1990;Friauf, 1994;Tardif et al, 2003).…”
Section: Higher Abundance Of Ca 2؉ -Binding and 14-3-3 Proteins In Thmentioning
confidence: 97%